The Use Of Code Mixing Between Indonesian And English In Indonesian Advertisement Of Gadis - Yessy Marzona (Fakultas Sastra Universitas Ekasakti, 2017)
This tendency is noticed when people use many ways of language variations to communicate or express their thought, ideas, and feelings. One example of these variations is code mixing. Code mixing is insertion of a piece of word other than that of your language, and you have no specific purpose or intention when doing communication. Code mixing is different from borrowing. Code mixing usually happens while people communicate in oral or written and in informal situation. In the case of code mixing, people sometimes mix two languages, particularly between national and a foreign language like English. However, code mixing does not only exist between the languages, there is also the mixing between national and regional languages. The researcher use GADIS to do this research. It was found that there were three forms of code mixing used in advertisement in GADIS. They were words, phrases and sentences which were put in the middle of the sentence of advertisements. Meanwhile, the use of code mixing in advertisements had many functions based on the purposes of communication, as we knew; advertisement was an advertiser’s way to communicate to the consumer, reader in this case. So, in this research it was found that there were three functions of the use of code mixing. They were greeting, informing, and rejecting.